Aspek hukum obligasi & sukuk - Sutedi, Adrian, 1966- (Jakarta : Sinar Grafika, 2009)
Legal aspects of conventional and Islamic bonds in Indonesia
Includes bibliographical references (p. 259-264)
Keywords: Bonds -- Law and legislation -- Indonesia; Bonds -- Religious aspects -- Islam